Intrahippocampal injection of endothelin-1: a new model of ischemia-induced seizures in immature rats - Tsenov, Grigorij; Matéffyová, Adéla; Mareš, Pavel; Otáhal, Jakub; Kubová, Hana (Epilepsia, 2007)
The goal of this study was to develop a new model of ischemia-induced seizures in immature rats using injection of vasoconstrictor Endothelin-1 (ET-1) into the brain. ET-1 (10, 20, or 40 pmol) was infused into the left dorsal hippocampus of freely moving Wistar rats 12 (P12) and 25 (P25) days old. Animals were then video/EEG-monitored for 100 min and monitoring was repeated 22 h later. Parameters of electrographic seizures (frequency and mean duration) as well as pattern of their behavioral correlates were evaluated. The pattern of behavioral seizures was used to develop model-specific scoring system. Cresyl violet and Fluoro Jade-B-staining were used to evaluate brain damage. Extension of the lesion was correlated with seizure severity. After ET-1-injection, seizures occurred in 83-100% animals of all age-and-dose groups and persisted for 24 h except P12 rats with 10 pmol. There were no differences in average seizure duration (18-40 s) or seizure frequency (3-7 seizures/100 min) among individual dose-groups. Between the 1st and 2nd observation period, total seizure duration decreased in 71% of P12 and 47% of P25 rats. Electrographic seizure activity was most frequently accompanied by clonus, incidence of more severe convulsions (barrel rolling or generalized clonic seizures) increased with dose of ET-1. Morphologic examination did not reveal any dose-related difference in damage severity, hippocampal damage was however more extensive in P12 compared to P25 animals. Seizure severity correlated positively with severity of the damage in both age groups. Our study presents focal injection of ET-1 into the brain as a new and practical model of ischemia-induced seizures in immature rats.
Keywords: financování organizované; Rats; Electroencephalography; Animals, Newborn; Epilepsy; epilepsie; Brain Ischemia; hipokampus; injekce; Rats, Wistar; mužské pohlaví; elektroencefalografie; Endothelin-1; novorozená zvířata; endotelin-1; krysa rodu Rattus; Financing, Organized; zvířata; Injections; Videotape Recording; potkani Wistar; ischemie mozku; videozáznam; Male; Hippocampus; Animals